Phytochemicals and The Ability of Plantago major Linn. Extract to Inhibit The Growth of Aeromonas hydrophila - Dewi, Annisa Farhana (Research Journal of Life Science, 2021)
Aeromonas hydrophila isgram-negative bacteria that can harm humans and major animals with poikilotherm properties such as fish and shrimp. These bacteria can cause hemorrhages in fish until death, causing fish farming production to fail. The use of medicinal plants has been trusted by people all over the world to overcome various disease problems, one of which is a disease caused by bacteria. Plantago major L. is known that able to inhibit the growth of both gram-positive and gram-negative bacteria. This study aims to find out the compounds contained in Plantago major L., using phytochemicals screening, FTIR, UV-VIS and antibacterial activity against A. hydrophila.This study extracts Plantago major L. known to contain polar compounds such as phenols, flavonoids, saponins, and tannins. The result of FTIR and UV-VIS strengthen the presence of phenols and flavonoids. Furthermore, extract Plantago major L. is known to be able to significantly inhibit the growth of A. hydrophila (P<0.05).